Chickpea, mungbean, cowpea and peanuts as substitutes for soybean curds - Mohamed, S.; Johan, Z.; Bakar, J. (Oxford University Press (OUP), 1989)
Acceptable beancurds could not be formed from chickpea, mungbean, cowpea and peanuts, when using the standard procedure used to make soybean curds. Firmness (rigidity) of the curd was proportional to the protein content; inversely proportional to the square of the starch content; and negatively correlated with the square of the fat content. Firmness also improved the taste of the curds. Satisfactory curds could be formed from legume sources other than soybean only after the partial removal of starch (in chickpea, mungbean and cowpea) or oil (in peanuts). Calcium sulphate was the best coagulant; optimum concentrations were 0.3% (0.02 M) of the milk; and optimal heating time was 15 min at 95°C. Stirring during coagulation aided formation of firmer gels. The rigidity moduli of the various curds were: soybean 51 000 N m−2; peanuts 2200 N m−2; chickpea 6000 N m−2; mungbean 11 000 N m−2; and, cowpea 29 000 N m−2. Chickpea and mungbean curds were rated as liked (2.0 and 1.8 respectively), almost as well as soybean curds (1.5); cowpea (3.1) and peanut (4.2) curds were less preferred.